A retrospective analysis of the Shinmoedake (Japan) eruption of 26–27 January 2011 by means of Japanese geostationary satellite data - Marchese, F.; Falconieri, A.; Pergola, N.; Tramutoli, V. (Journal of volcanology and geothermal research, 2014)
During the sub-plinian eruptions of Mt. Shinmoedake (Japan) on 26–27 January 2011 a significant amount of ash was emitted into the atmosphere, destroying thousands of hectares of farm land, causing air traffic disruption, and forcing the closure of four railroad lines located around the volcano. In this work, a retrospective analysis of these eruptive events is presented, exploiting the high temporal resolution of the Japanese Multi-functional Transport Satellites (MTSAT) data to study thermal volcanic activity, to identify and track volcanic ash, and to determine the cloud-top height, inferring information about eruption features and space-time evolution. We show that a strong and sudden increase in the thermal signal occurred at Mt. Shinmoedake as a consequence of above mentioned eruptive events, generating hot spots timely detected by the RSTVOLC algorithm for the first time implemented here on data provided by geostationary satellites. This study also shows that the emitted ash plume, identified by means of the RSTASH algorithm, strongly fluctuated in altitude, reaching a maximum height around 7.4km above sea level, in agreement with information provided by the Tokyo VAAC. The plume heights derived in this work, by implementing the widely accepted cloud-top temperature method, appear also compatible with the values provided by independent weather radar measurements, with the main differences characterizing the third sub-plinian event that occurred in the afternoon of 27 January. The estimates of discharge rate, the temporal trend of ash affected areas, and the results of thermal monitoring reported in this work seem to indicate that the third sub-plinian event was the least intense. In spite of some limitations, this study confirms the potential of Japanese geostationary satellites in effectively monitoring volcanoes located in the West Pacific region, providing continuous information also about such critical parameters of ash clouds as the plume height. Such information is useful not only for driving numerical models, forecasting ash dispersion into the atmosphere, but also for characterizing eruption features and dynamics. •Mt. Shinmoedake eruptions of 26–27 January 2011 are analyzed by using infrared MTSAT data.•Changes in thermal activity are investigated.•Capabilities in tracking ash clouds operationally from space are assessed.•Cloud-top height estimations are reported and assessed.•Eruption features and dynamics are inferred by using satellite observations.